Union of the Comoros : Staff Report for the 2012 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Financing Assurances Review-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Union of the Comoros. (IMF Staff Country Reports; Country Report ;, 2013)
The Comorian authorities have made steady progress in fiscal consolidation, reinvigorated their structural reform agenda, and gathered strong public support for sound macroeconomic policies. Macroeconomic developments have been largely positive, mostly thanks to improved policies. External competitiveness has improved step by step in the last year by the recent depreciation of the euro vis-a-vis the U.S. dollar. In the medium term, the government intends to seek further gains in fiscal consolidation and to accelerate reform of public enterprises and civil service.